Differential Induction of the ADAM17 Regulators iRhom1 and 2 in Endothelial Cells - Babendreyer, Aaron; Rojas-González, Diana M.; Giese, Anja Adelina; Fellendorf, Sandra; Düsterhöft, Stefan; Mela, Petra; Ludwig, Andreas (Frontiers in Cardiovascular Medicine, 2020)
Background: Endothelial function significantly depends on the proteolytic release of surface expressed signal molecules, their receptors and adhesion molecules via the metalloproteinase ADAM17. The pseudoproteases iRhom1 and 2 independently function as adapter proteins for ADAM17 and are essential for the maturation, trafficking, and activity regulation of ADAM17. Bioinformatic data confirmed that immune cells predominantly express iRhom2 while endothelial cells preferentially express iRhom1. Objective: Here, we investigate possible reasons for higher iRhom1 expression and potential inflammatory regulation of iRhom2 in endothelial cells and analyze the consequences for ADAM17 maturation and function. Methods: Primary endothelial cells were cultured in absence and presence of flow with and without inflammatory cytokines (TNFα and INFγ). Regulation of iRhoms was studied by qPCR, involved signaling pathways were studied with transcriptional inhibitors and consequences were analyzed by assessment of ADAM17 maturation, surface expression and cleavage of the ADAM17 substrate junctional adhesion molecule JAM-A. Results: Endothelial iRhom1 is profoundly upregulated by physiological shear stress. This is accompanied by a homeostatic phenotype driven by the transcription factor KLF2 which is, however, only partially responsible for regulation of iRhom1. By contrast, iRhom2 is most prominently upregulated by inflammatory cytokines. This correlates with an inflammatory phenotype driven by the transcription factors NFκB and AP-1 of which AP-1 is most relevant for iRhom2 regulation. Finally, shear stress exposure and inflammatory stimulation have independent and no synergistic effects on ADAM17 maturation, surface expression and JAM-A shedding. Conclusion Conditions of shear stress and inflammation differentially upregulate iRhom1 and 2 in primary endothelial cells which then results in independent regulation of ADAM17.